Kontribusi Usahatani Kakao Terhadap Pendapatan Petani Di Desa Mamullu Kecamatan Pana Kabupaten Mamasa - Heriawan, Reji; Salam, Suryawati; Baharuddin, Baharuddin (PALLANGGA: Journal of Agriculture Science and Research, 2024)
This research was conducted to determine the contribution of cocoa farming to farmers' income in Mamullu Village, Pana District, Mamasa Regency. This research took place from May to June 2023. 23 cocoa farmers were taken as samples. The method of data analysis uses income analysis and farming contributions. Based on the results of the study it can be concluded that the contribution of cocoa farming to farmer income is 21% which can be categorized as a source of farmer income, with an average cocoa farming income per year of Rp. 4,936,739,- and the average income of farmers per year is Rp. 30,958,043,-.. Penelitian bertujuan untuk mengetahui kontribusi usahatani kakao terhadap pendapatan petani di Desa Mamullu Kecamatan Pana Kabupaten Mamasa. Penelitian ini berlangsung pada bulan Mei – Juni 2023. Sampel diambil sebanyak 23 orang petani Kakao. Metode analisis data menggunakan analisis pendapatan dan kontribusi usahatani. Kontribusi usahatani kakao terhadap pendapatan petani adalah sebesar 21% dapat dikategorikan sebagai salah satu sumber pendapatan petani, dengan rata-rata pendapatan usahatani kakao per tahun sebesar Rp. 4.936.739,- dan rata-rata pendapatan petani per tahun Rp. 30.958.043,-.